Relationship of the humorous message, the trust of the group and participation in a Tabasco university - Balcázar, Jhoana Morales; Hugo Angulo Fuentes; Martha Libny Xicoténcatl Valencia (IJRDO -JOURNAL OF MATHEMATICS, 2021)
Related results from four studies carried out in different years in a southern university were analyzed, all of which refer to teacher-student and peer interaction of the Bachelor's degrees in Communication, Languages ​​and Educational Sciences. From the comparative analysis of results in each of the investigations, the objective consisted of inferring the relationship between the following variables: 1) the Freudian notion of the intentional joke, 2) other theoretical reflections of humor applicable in class and 3) its supposed effects that bring or distance interpersonal trust and oral participation. The correspondence of these variables has been evaluated and little thought has been given in tropical higher education, where humor constitutes an identity trait that should continue to be explored as an object of study, which represents a contribution that distinguishes this work. We conclude that the attitude of the participants should be self-critical when constructing and radiating humorous messages, depending on what they say, how they say it, what they do, what they project, how they identify the affective atmosphere of the group at the time and how they define their social responsibility as university students. . There is no doubt that you learn in happy and reliable environments and that there is no performance in climates of tension and fear.